Platelet-activating factor receptor (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Platelet-activating factor (PAF, 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) is an ether phospholipid mediator associated with platelet coagulation, but also subserves inflammatory roles. The PAF receptor (provisional nomenclature recommended by NC-IUPHAR [37]) is activated by PAF and other suggested endogenous ligands are oxidized phosphatidylcholine [73] and lysophosphatidylcholine [96]. It may also be activated by bacterial lipopolysaccharide [89].